2006
DOI: 10.1128/jvi.80.4.1972-1978.2006
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Prophylaxis and Therapy against Nipah Virus Infection in Hamsters

Abstract: Nipah virus (NiV), a member of the Paramyxoviridae family, causes a zoonotic infection in which the reservoir, the fruit bat, may pass the infection to pigs and eventually to humans. In humans, the infection leads to encephalitis with >40 to 70% mortality. We have previously shown that polyclonal antibody directed to either one of two glycoproteins, G (attachment protein) or F (fusion protein), can protect hamsters from a lethal infection. In the present study, we have developed monoclonal antibodies (MAbs) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 27 publications
2
74
0
Order By: Relevance
“…High levels of antibodies were induced by all vaccines, with ALVAC-G and ALVAC-F/G inducing higher neutralizing titers than the ALVAC-F vaccine. Previous work by Guillaume et al (17,19) indicated that antibodies against the G and F proteins have a crucial role in protection against NiV. The previously published vaccine study with golden hamsters using vaccinia virus vector reported an increase in antibody titers postchallenge, as detected by virus neutralization at 11 dpi (by ELISA at 5 dpi), and a decline at 18 dpi (17).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…High levels of antibodies were induced by all vaccines, with ALVAC-G and ALVAC-F/G inducing higher neutralizing titers than the ALVAC-F vaccine. Previous work by Guillaume et al (17,19) indicated that antibodies against the G and F proteins have a crucial role in protection against NiV. The previously published vaccine study with golden hamsters using vaccinia virus vector reported an increase in antibody titers postchallenge, as detected by virus neutralization at 11 dpi (by ELISA at 5 dpi), and a decline at 18 dpi (17).…”
Section: Discussionmentioning
confidence: 96%
“…It cannot be excluded that in case of the ALVAC-F/G group, where even the viral RNA was not detected, the vaccination led to sterile immunity. The presence of preexisting high levels of neutralizing antibodies at the time of challenge can, in case of NiV, lead to sterile immunity, as demonstrated by Guillaume and others (19).…”
Section: Discussionmentioning
confidence: 97%
“…It is almost without exception that all neutralizing antibodies to enveloped viruses are directed against the virus' envelope glycoproteins. Anti-G MAbs have been shown to be exceptionally potent in neutralizing NiV-and HeV-mediated fusion, as well as live virus infection (40), and a greater potency of NiV anti-G over anti-F MAbs in conferring passive protection of hamsters from NiV disease has recently been demonstrated (23).…”
Section: Discussionmentioning
confidence: 99%
“…Peptides designed to bind the F protein and block formation of the 6-HB inhibit HeV and NiV envelope glycoprotein-mediated membrane fusion in vitro (11)(12)(13). This mechanism of fusion Humoral immunity can clearly offer significant antiviral benefits, since hamsters were protected by passive transfer of antibodies against either NiV F or G (47,48). These studies suggest that immunization directed against the henipavirus envelope glycoproteins may be an effective vaccine strategy in humans or livestock.…”
Section: Henipavirus Biologymentioning
confidence: 99%